Performance Of Pandan Leaf Pigment For Dye Sensitized Solar Cell (Dssc): Effect Of Dye Extraction Temperature - Faiz, Mohamad Rodhi; Fahmi, Ahmad (JAVA Journal of Electrical and Electronics Engineering, 2016)
In Dye Sensitized Solar Cell (DSSC), the dye sensitizer plays the key role. Dye-sensitizer embedded in TiO2 will be able to absorb visible light up to approximately 800 nm and the energy conversion efficiency increase. In this study provides performance of pandan leaf pigment for Dye Sensitized Solar Cell (DSSC). The dye from pandan leaf pigment was extracted using distilled water solvent with various temperature, then investigated the absorption spectrum using UV-Vis spectroscopy. The extracted dye was adsorbed onto the surface of TiO2 based on Fourier Transform Infrared Spectroscopy (FTIR) analysis. The inhibition of crystallinity of TiO2 was likewise investigated by X-ray analysis.